Correlation of CD44v6 and type IV collagen immunohistochemical expression in borderline and malignant surface epithelial tumors - Abdul Ghany, Mohanad M.; AlKurtas, Mohammed A.; Hassan, Israa T. (AL-Kindy College Medical Journal, 2016)
Background: the difference in expression of type IV collagen in borderline tumors and ovarian carcinomas has been studied, but the association with adhesion molecules like CD44 have not gain enough interest. Objectives: The purpose of this study is to assess the expression of CD44v6 and type IV collagen status in borderline tumors and invasive ovarian carcinomas and the correlation between them to define the role of these molecules in tumor invasion and metastasis. Type of the study: A cross sectional study Methods: The study included a total of (101) formalin-fixed paraffin-embedded ovarian tissue blocks; of which (19) cases were borderline tumors and (82) cases were overt ovarian carcinomas. Sections from each block were immunohistochemically stained for CD44v6 and type IV collagen. Results: CD44v6 was significantly correlated with FIGO stage of borderline tumors (p=0.001) and ovarian carcinoma (<0.001) and with histological grade of ovarian carcinomas (p=0.004). There was significantly higher expression of type IV collagen in borderline tumors compared to invasive carcinoma(p<0.001) this significance was also seen in correlation to age, stage and grade of the invasive carcinoma, no significant differences in other clinicopathological features were found. There was negative correlation between CD44 v6 & type IV collagen which was statistically significance (P<0.05) in carcinoma but not in borderline tumors. Conclusions: Our data suggest that observed inverse correlation of type IV collagen expression with CD44v6 positivity in surface epithelial tumors indicates that these molecules may cooperate in the invasion and progression of ovarian carcinomas.